Expressions of Topo IIα and Ki67 in breast cancer and its clinicopathologic features and prognosis - Sun, Guangyu (Pak J Med Sci, 2019)
OBJECTIVE: Breast cancer is one of the most common malignant tumors in women, and its incidence in women has ranked the first place among all malignant cancers. The evolution of breast cancer which is highly heterogeneous is a complex biological process involving multiple factors, genes and stages. Therefore, studying the expression and interaction of related genes is of great significance to further revealing of the mechanism of the occurrence and development of breast cancer and reduction of its resistance to chemotherapy. The purpose of this study was to investigate expressions of Ki67 and Topoisomerase IIα (Topo IIα) in breast cancer tissues and to explore the relationship between expressions of Ki67 and Topo IIα and the pathological characteristics and prognosis of breast cancer. METHODS: Tissues with pathological changes and peripheral normal breast tissues were collected from 66 patients who underwent breast cancer treatment. Ki67 and Topo IIα in the breast cancer tissues and normal breast tissues were detected using immunohistochemical method. The relationships of Ki67 and Topo IIα with general clinicopathologic features and prognosis were analyzed. RESULTS: It was found that the positive expressions of Ki67 and Topo IIα in the breast cancer tissues were higher than those in the normal tissues; the positive expression rate of Ki67 was in a correlation with diameter of breast cancer and lymphatic metastasis (P<0.05); the positive expression rate of Topo IIα was in a correlation with clinical stage, diameter of cancer and lymphatic metastasis (P<0.05). Multi-factor logistic regression analysis suggested that lymphatic metastasis and clinical stage were the independent predictive factors for positive expression of Topo IIα and lymphatic metastasis was the independent predictive factor for positive expression of Ki-67. Breast cancer patients with negative Ki67 and Topo IIα had significantly higher local recurrence rate than those who had positive Ki67 and Topo IIα (P<0.05) after surgery. The median time to progression (TTP) of the patients with positive expression of Topo IIα was lower than that with negative expression (P<0.05). The median TTP of the patients with negative and positive expression of Ki67 had no significant difference (P>0.05). CONCLUSION: Topo IIα and Ki67 can be used for reflecting the proliferation activity of cancer cells and can affect the postoperative recurrence and survival time after surgery. They may be involved in the occurrence, development and metastasis of breast cancer. They are expected to be indicators in the prognosis prediction of breast cancer and potential treatment targets.